Characterizing farm households in Khotang, Eastern Nepal, through a quantitative farming systems typology - Zepeda, Adair; Cheesman, Stephanie; Neupane, Nilhari; Shrestha, Nirman; Shrestha, Ram Narayan; Amjath-Babu, T. S.; Karki, Saral; Gathala, Mahesh Kumar; Krupnik, Timothy J.; López Ridaura, Santiago (International Maize and Wheat Improvement Center, 2023)
Over the past centuries, the mid-hills of Nepal have been inhabited and cultivated by nomads, settlers and in the recent decades intensified farming systems. The system is constantly under systemic change due to farmers own actions and policies within the confines of biophysical resource envelope. Without proper design, the farming system has been characterised by high levels of degradation, expansion to marginal fragile landscapes, outmigration and high cost of production. These challenges pose higher productivity, financial and social risks. To sustainably manage the landscapes, reconfiguration of the farming system towards reduced risk and improved production is desirable. Coincidentally, this corresponds to Nepal’s devolution of planning to local authorities who demand the context specific redesign and resource management plans.